Value chain analysis of furniture: action research to improve power balance and enhance livelihoods of small-scale producers - Purnomo, H.; Achdiawan, R.; Parlinah, N.; Irawati, R.H.; Melati (2009)
Value chain analysis (VCA) has emerged since the 1990s as a novel approach for understanding how power, benefits and costs are embodied and distributed to various actors. The Indonesian furniture industry demonstrates a long chain of production to consumption, from raw material producers (tree growers), semi-finished producers, finished product producers, and retailers to exporters. Each actor is connected by intermediaries. Indonesian furniture, dominated by teak, contributed 2% of the global wood furniture trade (valued US$ 85 billion in 2007). Indonesian forest includes more than 35% of the world’s teak forests. The furniture industry provides employment and livelihoods to millions of people. This paper describes the value added distribution to all furniture actors, actions to strengthen small-scale producers, and global comparisons with other forest product value chains. The furniture value chain connects producers from Jepara District, the center of Indonesian furniture with annual exports of US$ 150 million, with furniture retailers in Europe, the USA, Australia and Japan. The problem is power imbalance throughout the value chain and unhealthy competition among producers, which result in poverty of small-scale producers, product quality degradation and an unsustainable furniture industry. The adaptation of small-scale producers to market demand is low. They are price takers rather than the price setters, as indicated by their decreasing bargaining power. We used VCA to hypothesize governance and institutional arrangement scenarios for more equitable power and income to sustain both the forest and the furniture industry. Following the VCA analysis, action research is being conducted. Researchers and furniture stakeholders have jointly developed plans and actions to strengthen the industry structure, improve value addition and improve livelihoods. To ensure local and national impacts, we have collaborated with the Jepara Furniture Multi-stakeholder Forum, the Jepara local government, the Forestry Research and Development Agency (FORDA) of the Indonesia Ministry of Forestry, and Bogor Agricultural University. At international level, we are comparing this study with lesson learned from value chains of bamboo in China, honey bee in Zambia, potential for reducing emissions from deforestation and degradation (REDD) credit in Indonesia, and palm heart/ palmito in Brazil.